Convergence Results for Total Asymptotically Nonexpansive Monotone Mappings in Modular Function Spaces - Rashid, Maliha; Kalsoom, Amna; Yao, Shao-Wen; Ghaffar, Abdul; İnç, Mustafa (Wiley, 2021)
In this article, we consider an extensive class of monotone nonexpansive mappings. We use S-iteration to approximate the fixed point for monotone total asymptotically nonexpansive mappings in the settings of modular function space.
Keywords: Fixed-Point Theorem